The comparative advantage of the tax regime of the non-habitual resident in Portugal - Amorim, José Campos; Instituto Superior de Contabilidade e Administração do Porto (2018)
The tax regime of the non-habitual resident (RNH) is particularly attractive for non-residents who practice high value-added professional activities, and for employed or self-employed workers, retired people, or members of statutory bodies of legal entities who want to obtain residency in Portugal in order to receive tax benefits. In a comparative analysis with other countries, the Portuguese regime confers greater tax benefits to non-residents who intend to establish their residence in Portugal.